Tissue Valve Replacement for Severe Calcified Pulmonary Stenosis: First time in BSMMU - Bulbul, Rezwanul Haque; Khan, Omar Sadeque; Sunny, Mohammad Samir Azam; Sarker, Swadesh Ranjan; Nuruzzaman, Mostafa (University Heart Journal, 2014)
Pulmonary valve replacement for pulmonary regurgitation is a common practise. Pulmonary stenosis relief or after release of right ventricular outflow tract obstruction, progressive pulmonary regurgitation leading to biventricular failure is a big problem. If early pulmonary valve replacement done by homograft or tissue valve then we can overcome this problem. In our case report we have done pulmonary valve replacement by Edward life science Tissue valve for calcified pulmonary valve. And our patient showed a good response after valve replacement. DOI: http://dx.doi.org/10.3329/uhj.v9i1.19514 University Heart Journal Vol. 9, No. 1, January 2013; 54-55